A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China - Yang, Jian-Huan; Wang, Jian; Wang, Ying-Yong (Zootaxa, 2018)
We describe a new horned toad species of the genus Megophrys from Yingjiang County of Yunnan Province, China. The new species, Megophrys feii sp. nov., can be distinguished from its congeners by a combination of the following characters: (1) body slender and small (SVL 24.3–25.1 mm in four males, 28.2–28.9 mm in two females); (2) head length about equal to head width (HDL/HDW 0.97–0.99); (3) tympanum circular and distinct; (4) maxillary teeth present; (5) vomerine ridges and vomerine teeth absent; (6) tongue round, slightly notched posteriorly; (7) tibia long (TIB/SVL 0.48–0.52 in four males, 0.54–0.55 in two females), shanks overlapping when thighs are held at right angles to the body; (8) dorsal skin distinctly granular and densely covered with small tubercles; (9) lower flanks and lateral sides of belly scattered with small but prominent, white, tubercles; (10) webbing between toes rudimentary; (11) lateral fringes on toes moderate to wide; (12) breeding males without nuptial pads and spines on fingers; (13) protruding projection posterior to cloaca present in both sexes; (14) groin and ventral thigh coloration in life not contrasting with surrounding regions; (15) the presence of an indistinct and small horn-like tubercle at the edge of the eyelid; and (16) an advertisement call with a dominant frequency of 4.74–4.91 kHz (at 18 ˚C). To date, the new species has only been found at its type locality in stream areas in montane evergreen broadleaf forests between 700–1200 m elevation.